Merancang Strategi Pengembangan Keterampilan Argumentatif: Menanamkan Pemikiran Kritis Ilmiah ke dalam Pembelajaran Sistem Pencernaan untuk Siswa Sekolah Menengah Atas - Al Khudri Sembiring; Marta Dinata; Ramanda Rizky; Rahmat Ramadansur; Danil Alpito (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Many students still experience difficulties in developing argumentation skills because learning activities often emphasize memorization rather than analytical reasoning. Therefore, this study aims to examine the effectiveness of the Scientific Critical Thinking in improving students’ argumentation skills in learning the human digestive system. This study employed a quasi-experimental design with a pretest–posttest control group framework involving two groups of senior high school students, namely the experimental and control groups. Data were collected through pretests, posttests, and an argumentation skills questionnaire developed based on the Toulmin Argument Pattern, which includes the indicators of claim, data, warrant, backing, qualifier, and rebuttal. The research instruments were validated prior to implementation to ensure reliability and accuracy in measuring students’ argumentation abilities. The collected data were analyzed using IBM SPSS Statistics through normality tests, homogeneity tests, and an independent samples t-test. The results indicate that students who participated in learning using the SCT model demonstrated significantly higher argumentation skills compared to those who experienced conventional instruction. These findings suggest that integrating the SCT learning model effectively enhances students’ critical reasoning, scientific argumentation, and deeper conceptual understanding in biology learning, thereby supporting the development of essential competencies required in 21st-century education.